2019
DOI: 10.1016/j.cub.2019.08.022
|View full text |Cite|
|
Sign up to set email alerts
|

Precise Coordination of Three-Dimensional Rotational Kinematics by Ventral Tegmental Area GABAergic Neurons

Abstract: The ventral tegmental area (VTA) is a midbrain region implicated in a variety of motivated behaviors. However, the function of VTA GABAergic (Vgat+) neurons remains poorly understood. Here, using threedimensional motion capture, in vivo electrophysiology, calcium imaging, and optogenetics, we demonstrate a novel function of VTA Vgat+ neurons. We found three distinct populations of neurons, each representing head angle about a principal axis of rotation: yaw, roll, and pitch. For each axis, opponent cell groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Our design is directly inspired by the hierarchical organization of the motor system in vertebrates (16), and by its ability to pursue a hierarchy of goals in parallel, despite a complex and unpredictable environment (52). This basic design is in agreement with extensive experimental work in neuroscience (5, 6, 7, 8, 20, 21, 26, 27), and the efficacy of this design supports input control hierarchies as a working model for how the nervous system generates goal-directed behavior.…”
Section: Discussionsupporting
confidence: 78%
“…Our design is directly inspired by the hierarchical organization of the motor system in vertebrates (16), and by its ability to pursue a hierarchy of goals in parallel, despite a complex and unpredictable environment (52). This basic design is in agreement with extensive experimental work in neuroscience (5, 6, 7, 8, 20, 21, 26, 27), and the efficacy of this design supports input control hierarchies as a working model for how the nervous system generates goal-directed behavior.…”
Section: Discussionsupporting
confidence: 78%
“…2a) from FreiPoses' 3D reconstructions and combined them with extracellular recordings in the rat motor cortex. Previous work on the neuronal representation of body poses in rodents relied on marker-based systems [4,12]. Applying FreiPose to one recording session of a freely exploring rat combined with simultaneous neural recordings revealed that almost half of the recorded neurons in motor cortex was tuned to postural features (42.4%, 28/66 cells, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The neural activity that occurs in between experimenter-defined events is usually neglected. However, recent work has shown that continuous behavioral measurements with high spatial and temporal resolution can reveal previously neglected relationships between neural activity and behavior (Barter et al, 2014(Barter et al, , 2015aKim et al, 2014Kim et al, , 2019Bartholomew et al, 2016;Hughes et al, 2019). Our system demonstrates that, with continuous behavior measures, neural activity outside of these observed defined timepoints becomes intelligible.…”
Section: Discussionmentioning
confidence: 78%
“…To determine the relationship between such continuous measures of movement and neural activity, we recorded single unit activity from the VTA of welltrained mice performing the fixed-time task (n = 2, Figure 5A), isolating spiking activity from putative GABAergic neurons in this region. Recent work showed that these neurons can control head angle continuously in freely moving mice (Hughes et al, 2019), but it is unclear how their activity may be related to force exerted by head-fixed mice.…”
Section: Neural Recordings Of Vta Activity While Measuring Whole Bodymentioning
confidence: 99%